INHIBITION OF PRIMARY PRODUCTION AS INDUCED BY HEAVY METAL IONS ON PHYTOPLANKTON POPULATION OFF COCHIN - Kaladharan, P; Alavandi, S V; Pillai, V K; Balachandran, V K (Indian Journal of Fisheries, 2011)
The effect of five metals (Cd, Ni, Cr, Pb and Hg) at different concentrations below and above tolerance limits, in the primary productivity off Cochin was investigated. It was observed that cadmium, nickel, lead, chromium and mercury even at low concentrations were found inhibiting the primary productivity. Among the metals tested, nickel apfieared to be the least toxic and mercury the most toxic in their inhibitory effect. It was evident that the synergistic effect of inhibition was more acute when the metals were present in combination than each metal individually.